PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP NEGERI 25 PADANG - Hayati, Sisri (Jurnal Edukasi dan Penelitian Matematika, 2023)
Due to the insufficient problem-solving skills of VII pupils, this study was conducted. To counteract this, research was conducted to enhance students' problem-solving abilities through the Contextual Teaching and Learning (CTL) approach. The purpose of the study is to determine and describe the mathematical problem-solving ability of seventh-grade students at SMP Negeri 25 Padang whose learning with the CTL approach is superior to their mathematical problem-solving ability with the traditional learning model. And to understand and describe the development of mathematical problem-solving skills in students using the CTL method. This investigation utilised a quasi-experimental design. The design employed is a "Pretest-Posttest Control Group Design" with a random sampling strategy. Using the normality test, the homogeneity test, and the hypothesis test, mathematical problem-solving ability data was analysed. Based on the hypothesis test, P = 0.015 was obtained. Since P = 0.05, the null hypothesis H0 should be rejected. This suggests that students whose education utilises the CTL approach are more adept at solving mathematical problems. Thus, CTL-based learning strategies influence students' ability to solve mathematical problems.Keywords– Contextual Teaching And Learning (CTL), Pemecahan Masalah Matematis, Model Pembelajaran Konvensional